2005
DOI: 10.1542/peds.2005-0466
|View full text |Cite
|
Sign up to set email alerts
|

Clown Doctors as a Treatment for Preoperative Anxiety in Children: A Randomized, Prospective Study

Abstract: ABSTRACT. Background. The induction of anesthesia is one of the most stressful moments for a child who must undergo surgery: it is estimated that 60% of children suffer anxiety in the preoperative period. Preoperative anxiety is characterized by subjective feelings of tension, apprehension, nervousness, and worry. These reactions reflect the child's fear of separation from parents and home environment, as well as of loss of control, unfamiliar routines, surgical instruments, and hospital procedures. High level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
275
4
36

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(327 citation statements)
references
References 26 publications
12
275
4
36
Order By: Relevance
“…Studies have shown positive effects of these activities on the children, and it has been suggested that medical clowns should become an integral part of the health team (Kocherov et al, 2016; Ofir et al, 2016; Tener, Ofir, Lev-Wiesel, Franco, & On, 2016; Wolyniez et al, 2013). However, other studies showed a more negative attitude and suggested that the presence of clowns may interfere with medical routines and that children did not want a clown present during tests or medical procedures (Mansson et al, 2013; Vagnoli et al, 2005; Van Venrooij & Barnhoorn, 2017). In our study, most participants also did not support the idea of medical clowns being present during medical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown positive effects of these activities on the children, and it has been suggested that medical clowns should become an integral part of the health team (Kocherov et al, 2016; Ofir et al, 2016; Tener, Ofir, Lev-Wiesel, Franco, & On, 2016; Wolyniez et al, 2013). However, other studies showed a more negative attitude and suggested that the presence of clowns may interfere with medical routines and that children did not want a clown present during tests or medical procedures (Mansson et al, 2013; Vagnoli et al, 2005; Van Venrooij & Barnhoorn, 2017). In our study, most participants also did not support the idea of medical clowns being present during medical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a clown has been found to reduce the child’s anxiety (Dionigi, Sangiorgi, & Flangini, 2014; Felluga et al, 2016; Goldberg et al, 2014; Kocherov et al, 2016; Meiri, Ankri, Hamad-Saied, Konopnicki, & Pillar, 2016; Messina et al, 2014; Vagnoli, Caprilli, & Messeri, 2010; Vagnoli, Caprilli, Robiglio, & Messeri, 2005; Weintraub et al, 2014) and feelings of boredom, loneliness and sadness (Finlay, Baverstock, & Lenton, 2014; Mansson, Elfving, Petersson, Wahl, & Tunell, 2013; Meiri et al, 2016). Also, a few studies showed that a clown intervention is able to reduce anxiety in parents (Agostini et al, 2014; Fernandes & Arriaga, 2010; Wolyniez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chez l'enfant, deux intéressantes études randomisées et contrôlées ont évalué la « clown-thérapie ». La présence de clowns en préopératoire s'est révélée être efficace sur le score d'anxiété dans les deux cas : n = 40, score m-YPAS = 30.75 vs. 50, p < 0.05 [40], n = 55, score m-YPAS = 42 vs 50, p < 0.05 [7].…”
Section: Approches Psychologiquesunclassified
“…Um estudo feito com crianças, prestes a serem submetidas a uma cirurgia, mostrou que a presença de palhaços provocando o riso (juntamente com os pais) durante a aplicação da anestesia, reduziu os níveis de ansiedade tanto da criança como dos pais durante o pré-operatório (VAGNOLI et al, 2005).…”
Section: O Riso: Uma Abordagem Atualunclassified